Why Be Accountable? Exploring Voluntary Accountability of Australian Private Ancillary Funds. Issue 3 (30th May 2017) - Williamson, Alexandra; Luke, Belinda; Furneaux, Craig
Abstract: The aim of this paper is to consider why Private Ancillary Funds (PAFs), endowed philanthropic foundations with no public reporting requirements, engage in accountability in its various forms. This exploratory, qualitative study reports on perspectives on accountability from 10 semi‐structured interviews with PAF managers and/or trustees from three Australian states. Through the lens of March and Olsen's (2011) logics of action and Karsten's (2015) typology of motivational forms for voluntary accountability, findings show that although logics of appropriateness and consequentiality explain many reasons why PAFs engage in voluntary accountability, some reasons do not fit comfortably within either logic. The findings challenge conceptions embedded in much non‐profit accountability literature that motivations for and purposes of accountability are linked with sustainability and survival. By examining this subset of non‐profit organisations subject to limited regulatory accountability, a clearer understanding of motivations for voluntary accountability is achieved. Abstract : This paper examines why Private Ancillary Funds ‐ endowed philanthropic foundations with no public reporting requirements, engage with accountability when financial sustainability and legitimacy are not concerns. Perspectives on accountability are gained from 10 interviews with PAF managers and/or trustees from three Australian states. Findings show that while logics of appropriateness (doing the right thing) and consequentiality (assessing costs and benefits) explain many reasons why PAFs engage in voluntary accountability, there are other motivations belonging in a hybrid space of emotions.